Comportamento do chumbo em um solo típico de uma área de destruição de munição - Oliveira, Shirlei Aparecida de (2017)
The soil contamination by lead was verified in area used for ammunition destruction activity. This study aims to evaluate the retention and mobility of lead in a typical soil of area where this activity is developed. Therefore, samples were collected from the horizons of a soil profile located outside the property and without previous contamination. The Langmuir isotherm was considered the most appropriate to represent the sorption experimental data. The Hydrus-1D code proved to be a useful tool to simulate PB transport in the soil.